Large vocal repertoires do not constrain the dear enemy effect: a playback experiment and comparative study of songbirds. (August 2016) - Moser-Purdy, Christopher; Mennill, Daniel J.
Abstract : Many territorial animals are less aggressive towards neighbours than they are towards strangers. This phenomenon is known as the 'dear enemy' effect and it occurs because strangers represent a considerably higher threat to territory take-over compared to neighbours. Some evidence has suggested that large repertoires may constrain neighbour–stranger discrimination. We tested whether songbirds with large repertoires exhibit neighbour–stranger discrimination, conducting a playback study on a songbird with a large vocal repertoire, and a comparative analysis of the dear enemy effect across all published studies of songbirds. In our playback study, we broadcast neighbour and stranger songs within the breeding territories of red-eyed vireos, Vireo olivaceus, a songbird species with a large song repertoire (ca. 50 songs per individual). Vireos responded significantly more aggressively to playback of stranger versus neighbour songs; subjects approached closer to the loudspeaker, had a lower latency to approach the loudspeaker, spent more time near the loudspeaker and sang more soft songs during stranger trials than during neighbour trials. We examined song sharing between red-eyed vireos and found low levels of song sharing between neighbours, suggesting that red-eyed vireos may discriminate among conspecifics based on individually distinctive song types. We then conducted a comparative analysis of neighbour–stranger discrimination across the published literature on songbirds, using a phylogenetically controlled analysis to explore whether species with large repertoires are less likely to discriminate between neighbours and strangers. Across 34 species, we found no evidence that songbirds with large repertoires are constrained in their ability to distinguish between neighbours and strangers. We conclude that large song repertoires do not inhibit neighbour–stranger discrimination in red-eyed vireos specifically, or songbirds generally. Highlights: In theory, large repertoires may constrain neighbour–stranger discrimination. We used playback to test discrimination in a songbird with a large repertoire. Playback subjects capably discriminated, showing a stronger response to strangers. We then used a comparative analysis to explore this idea across 34 songbirds. We found no effect of repertoire size on neighbour–stranger discrimination ability.